On a hypothesis concerning Hamiltonians of canonical systems - Sakhnovich, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We present a classification of canonical systems and show that, under certain conditions, Hamiltonians belonging to the same class are linearly similar.